1997
DOI: 10.1111/j.1365-2044.1997.103-az0100.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal intubation conditions after one minute: rocuronium and vecuronium, alone and in combination

Abstract: SummaryRocuronium is a recently introduced nondepolarising neuromuscular blocking agent with a rapid onset and intermediate duration of action. Experimental observations have suggested that during onset it acts synergistically with other nondepolarising agents, but that at a steady state the combined action is additive. In order to investigate whether synergism during onset produces a clinical benefit we performed the following study of tracheal intubation conditions. Consenting patients presenting for electiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Synergism of combination of rocuronium and vecuronium was also observed by England AJ and colleagues, 7 who noted excellent to good intubating conditions at 60sec in 90% of patients receiving combination of vecuronium and rocuronium. Neeti M and colleagues 8 also noted excellent to good intubating conditions at 60sec in 93.3% of patients receiving combination of vecuronium and rocuronium.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Synergism of combination of rocuronium and vecuronium was also observed by England AJ and colleagues, 7 who noted excellent to good intubating conditions at 60sec in 90% of patients receiving combination of vecuronium and rocuronium. Neeti M and colleagues 8 also noted excellent to good intubating conditions at 60sec in 93.3% of patients receiving combination of vecuronium and rocuronium.…”
Section: Discussionmentioning
confidence: 69%
“…7,8 Nigrovic and colleagues 9 have postulated that the neuromuscular blocking agents belonging to different chemical groups (Isoquionoline or aminosteroid) display an inverse pattern of affinities for the two α-subunits and, when present together, produce a synergistic neuromuscular block. This hypothesis does not satisfactorily explain the synergistic behaviour of the combination of structurally similar rocuronium and vecuronium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…England, M. F. Morgarson and S. A. Feldman studied comparison of mixture of vecuronium and rocuronium with either vecuronium or rocuronium for quality of condition for tracheal intubation at one minute. (15) Excellent intubation conditions were achieved in 57% of the rocuronium group, 70% of mixture group and 27% of rocuronium group. Adequate intubating conditions are dependent on depth of anaesthesia, skill of endoscopist and muscle relaxation.…”
Section: Group Excellentmentioning
confidence: 85%
“…However, Meretoja et al [23] showed synergistic interaction between atracurium and mivacurium which are structurally benzylisosquinolines. Similarly, England et al [24] showed that a mixture of rocuronium and vecuronium acts synergistically during early part of their action. e present study examined the combination of pancuronium and rocuronium to evaluate the possibility of synergism between the two.…”
Section: Discussionmentioning
confidence: 99%